Fishing Community Livelihood Development and Its Implications for Spatial Planning - Iva, Nur Ilmi (Journal of Civil Engineering and Planning (JCEP), 2025)
Labuhan Haji is one of the fishing villages characterized by a low standard of living among its residents. The economic conditions of the fishing community are concerning, despite the logical assumption that various means. In addition to working as fishermen, many also engage in agricultureal labor or small-scale trading. However, these alternative occupations are not always located within the village or in nearby areas, which results in diverse spatial requirements. This study aims to examine the relationship between the development of livelihood strategies among the fishing community and their impact on the spatial pattern of the village. A mixed-methods approach was employed, combining quantitative analysis using a spatial approach focused on human activities. The scoring results indicate that the agricultural sector received the higest score, totaling 1,090 with an average of 77.85%. correlation anlysis further reveals that the fuctional relationship between agriculture and spatial pattern variables yielded a correlation score of 9, indicating a strong correlation with variables such as transportation routes, physical form, and the distribution of facilities.